1994
DOI: 10.1128/aem.60.2.454-458.1994
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Thermophilic Fungi in Mushroom Compost, with Emphasis on Scytalidium thermophilum and Growth Stimulation of Agaricus bisporus Mycelium

Abstract: Twenty-two species of thermophilic fungi were isolated from mushroom compost. Scytalidium thermophilum was present in the compost ingredients, fresh straw, horse droppings, and drainage from compost and dominated the fungal biota of compost after preparation. Of 34 species of thermophilic fungi tested, 9 promoted mycelial growth of Agaricus bisporus on sterilized compost: Chaetomium thermophilum, an unidentified Chaetomium sp., Malbranchea sulfurea, Myriococcum thermophilum, S. thermophilum, Stilbella thermoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 26 publications
(16 reference statements)
1
36
0
Order By: Relevance
“…Together these data suggested that the enzyme was a monomeric protein. This value was similar to that reported for b-glucosidases from Humicola grisea [9,10], which is considered a synonym of S. thermophilum [11]. Isoelectric focusing (IEF-PAGE) of the purified b-glucosidase indicated a pI of about 6.5, higher than that of most microbial b-glucosidases, which are acidic proteins with pI values ranging from 3.5 to 5.5 [22].…”
Section: Molecular Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…Together these data suggested that the enzyme was a monomeric protein. This value was similar to that reported for b-glucosidases from Humicola grisea [9,10], which is considered a synonym of S. thermophilum [11]. Isoelectric focusing (IEF-PAGE) of the purified b-glucosidase indicated a pI of about 6.5, higher than that of most microbial b-glucosidases, which are acidic proteins with pI values ranging from 3.5 to 5.5 [22].…”
Section: Molecular Propertiessupporting
confidence: 85%
“…Moreover, a few microbial b-glucosidases are known to be 0378 activated by glucose [7,8]. Thermophilic filamentous fungi are good producers of b-glucosidases with high thermal stability [9,10], and among these Scytalidium thermophilum is an efficient consumer of cellulosic materials [11]. This report describes the properties of a glucose-and xylose-activated b-glucosidase from this fungus.…”
Section: Introductionmentioning
confidence: 98%
“…Scytalidium thermophilum ( Cooney & Emerson ) Austwick , Torula thermophila , Humicola grisea var. thermoidea , and Humicola insolens ( T opt 40 °C, T max 58 °C) have been commonly found in mushroom composts, nesting litter of chickens, soil, horse dung and wood chips, and been regarded as a potential resource for polysaccharide‐degrading enzymes and trehalase . Our previous investigation on the distribution of thermophilic fungi in Tengchong Hotspring National Park in Yunnan, China, revealed that the strains of Thermomyces lanuginosus and Scytalidium thermophilum were found in all the sampling sites and to be very prevalent with the frequencies of occurrence at 34.78 % and 28.26 %, respectively …”
Section: Introductionmentioning
confidence: 99%
“…The microbial ecology of the substrate is the underlying drive of the composting process and has been the impetus of several studies in the past, mainly for A. bisporus cultivation. Most of these studies used culture-dependent methods to isolate the microbes from compost (Fordyce 1970;Fergus 1964;Fermor et al 1979;Straatsma et al 1989Straatsma et al , 1994.…”
Section: Introductionmentioning
confidence: 99%